PENGARUH PARTISIPASI DAN PERMODALAN ANGGOTA TERHADAP KESEJAHTERAAN ANGGOTA KOPERASI UNIT DESA BULURAN KENALI KECAMATAN TELANAIPURA KOTA JAMBI - Pratiwi Indah Sari, Larasati (Universitas Batanghari Jambi, 2018)
AbstractThis study aims to determine the description of respondents and the influence of participation and capital of members together, on the welfare of members of the Village Unit Cooperative Bulungan Kenali District Telanaipura Jambi City. Based on the data analysis on the results of research that there is a significant influence between the participation and capital of members together, to the welfare of members of the Village Unit Cooperative Bulungan Kenali District Telanaipura Jambi City. With result of model summary R = 0,311 and R Square = 0,297. In ANOVA, the value F = 9.179 with α (sig) = 0,000. Because α (Sig) < 0.05, then regression can be used to predict participation and capital at 95% confidence level. Based on the value of B constant and X, we can make a regression equation that is Y = a + X1 + X2 = 29,610 + 0,198 + 0,182. And, for t arithmetic X1 = 2.895, and t arithmetic X2 = 2.628 then t arithmetic> t table. This means that t count > t table. This means that the t test shows that participation (X1) and capital (X2) has a positive and significant influence on the welfare of members (Y) of Jambi Village Village Village Cooperative Unit. Keyword : Participation, Permodalan, Welfare Member, Village Unit Cooperative.